Biomechanical investigation of individual with over-pronation and over-supination foot during walking / Nur Saibah Ghani - Nur Saibah , Ghani (2020)
Over-pronation and over-supination foot conditions are foot deformity that can lead to unstable ankle and subtalar joint during walking. They are define as condition where the foot roll in and out excessively from its neutral line and can lead to misalignment of the foot and leg in human in which can create abnormal gait cycle. Therefore, the purposes of this study are to analyze the foot-ankle joint biomechanical behavior including the range of motion, joint moment, joint power and GRF in a complete gait cycle for all subjects in this study and to compare the foot-ankle biomechanical behavior between normal foot with over-pronation and over-supination foot condition during walking. 20 subjects were volunteer but only 16 passed the selection test and divided into three groups; normal subjects (n=2), over-pronation (n=7) and over-supination (n=7). Motion analysis system was used to observe and analyze the gait cycle in individual with over-pronation and over-supination conditions. The raw data that we got from motion analysis will be statistically analyzed using the Nexus 1.3 and MATLAB_R2019a software. The result observed were kinematics and kinetic parameter of foot during walking. The statistical analysis done to compare normal foot with OP foot condition shows that the ankle joint during the initial contact was below 5° for all subjects. Subject 2 shows the lowest ankle angle during initial contact while for mid stance phase, subject 3 shows the highest ankle angle which was 24.15° on left foot and 28.30° on right foot. From the ANOVA test, the p-value for ankle joint angle was less than 0.05, which indicates that there was significant difference between all the subjects. For joint moment and power the p-values found was less than 0.05 which indicates there was significance differences between over-pronation compare to normal foot condition. While for subjects with over-supination condition, they tends to be in plantar flexion condition during heel strike phase rather than in neutral position because the high arch put the foot in plantar flexion position such as subject 1(-0.69), subject 3 (- iv 0.33°), subject 5 (-0.38°) and subject 7 (-4.55°). While the normal subject starts this phase at neutral position (0°) and a little dorsiflexion (2.97°). The statistical analysis for kinetic and kinematic data when comparing over-supination foot condition with normal foot condition shows that the p-values were more than 0.05 that indicates there were no significant differences between these two conditions. Therefore, this research concluded that the analyzed done on kinetic and kinematic data to demonstrate that the ankle joint angle, moment, power and GRF does in fact influence by the condition of the foot and can cause deformities if no proper treatment was done.